The creation of a community of practice to qualify teachers in the integration of ICTs into foreign language learning and teaching processes - Bedoya-González, Juan Rodrigo; Betancourt-Cardona, Miguel Orlando; Villa-Montoya, Fabio León (Íkala, Revista de Lenguaje y Cultura, 2018)
This article presents the development and final results of a research project, involving the creation of a community of practice (COP) with a group of language teachers, interested in learning and building knowledge about pedagogical and instrumental aspects in integrating ICTs into their teaching practices. COP members worked collaboratively during 2 semesters designing the theoretical foundations, creating video tutorials and designing and implementing encouraging activities to motivate more colleagues to become members. Findings show how the core group and some COP active members increased their pedagogical and instrumental knowledge about the integration of ICT into L2 learning and teaching processes. Involving new members in the encouraging activities was a permanent challenge for the core group of the COP.